Diversity, chemical constituents and biological activities of endophytic fungi from Alisma orientale (Sam.) Juzep. - Shen, Nayu; Chen, Zhao; Cheng, GuiXin; Lin, Wenjie; Qin, Yihan; Xiao, Yirong; Chen, Hui; Tang, Zizhong; Li, Qingfeng; Yuan, Ming; Bu, Tongliang (Frontiers in Microbiology, 2023)
The dried tuber of Alisma orientalis(Sam.)Juzep.(AOJ) is a traditional Chinese medicine with high medicinal value. The endophytic fungi of medicinal plants are a treasure house of natural compounds. However, there is a lack of research on the diversity and biological activity of the endophytic fungi of AOJ. In this study, high throughput sequencing technology was used to study the diversity of endophytic fungi in the roots and stems of AOJ, and the endophytic fungi with high output of phenols and flavonoids were screened by chromogenic reaction, and the antioxidant, antibacterial activities and chemical constituents of the crude extracts of their fermentation broth were studied. A total of 3426 ASVs belonging to 9 phyla, 27 classes, 64 orders, 152 families, 277 genera were identified from the AOJ. There were significant differences in the endophytic fungal communities of AOJ roots and stems, as well as in the endophytic fungal communities of triangular AOJ and circular AOJ. In addition, 31 strains of endophytic fungi were isolated from AOJ, of which 6 strains had good antioxidant and antibacterial activities. The crude extract of YG-2 had the strongest free radical scavenging ability and bacteriostatic ability, and its IC50 DPPH, IC50 ABTS and IC50 ·OH were 0.009 ± 0.000 mg/mL, 0.023 ± 0.002 mg/mL and 0.081 ± 0.006 mg/mL respectively. The results of LC-MS showed that the main component of the crude extract of YG-2 was Caffeic acid(10.12 μmol/g). Overall, the results of this study preliminarily elucidated the diversity and community composition of endophytic fungi, indicating that AOJ endophytic fungi have abundant secondary metabolites and good antioxidant and antibacterial activities. It provided important reference for further research, development and utilization of AOJ endophytic fungi, and provided a theoretical basis for the further development of endophytic fungus YG-2(Chaetomium globosum) as a source of antioxidants.